"Backwards and in High Heels": The Invisibility and Underrepresentation of Femme(inist) Administrative Labor in Academia. Issue 2 (2nd April 2020) - Inayatulla, Shereen; Robinson, Heather
Abstract : This article examines the ways in which embodiments of femme within administrative academic settings intervene in dominant discourses that (incorrectly) frame us as being "in service" of male-identified colleagues, supervisors, and institutionalized heteropatriarchies. We posit femme as an important and complex counternarrative to the heterocentric, cissexist, and masculinist discourses that are ubiquitous within academic administration in both historical and present-day contexts. Additionally, we consider femme as a site of resistance to feminized discourses of nurturance and of (re)productivity. In this collaborative project, we study the labor involved in administering an English Department and a Writing Program at a four-year public college, interrogating, through autoethnographic reflections and analyses, the ways in which this service labor often falls to/gets thrust upon those of us who identify as femme faculty members. Our article illustrates how we resist the imposition of care work and assert our own agency while conducting administrative work on our own, femme, terms. We offer a list of usable interventions to common, predictable, yet sometimes disorienting situations, and although we do not advance these responses as easy conclusions to problematic interactions, we consider how this list might aid femme administrators in managing quotidian, misguided, at times hostile scenarios. Our work calls allies and comrades to identify systemic asymmetries and generate collaborative solutions within a paradigm of affirmation: One that places a commitment to "femme witnessing" at its center.